OsWRKY28 Regulates Phosphate and Arsenate Accumulation, Root System Architecture and Fertility in Rice - Wang, Peitong; Xu, Xuan; Tang, Zhong; Zhang, Wenwen; Huang, Xin-Yuan; Zhao, Fang-Jie (Frontiers in Plant Science, 2018)
WRKYs are transcriptional factors involved in stress tolerance and development of plants. In the present study, we characterized OsWRKY28, a group IIa WRKY gene, in rice, because its expression was found to be upregulated by arsenate exposure in previous transcriptomic studies. Subcellular localization using YFP–OsWRKY28 fusion protein showed that the protein was localized in the nuclei. Transgenic rice plants expressing pOsWRKY28::GUS suggested that the gene was expressed in various tissues in the whole plant, with a strong expression in the root tips, lateral roots and reproductive organs. The expression of OsWRKY28 was markedly induced by arsenate and other oxidative stresses. In a hydroponic experiment, loss-of-function mutation in OsWRKY28 resulted in lower accumulation of arsenate and phosphate concentration in the shoots. The mutants showed altered root system architecture, with fewer lateral roots and shorter total root length than wild-type plants. In a soil pot experiment, the mutants produced lower grain yield than wild-type because of reduced fertility and smaller effective tiller numbers. Transcriptomic profiling using RNA-seq showed altered expression in the mutant of genes involved in the biosynthesis of phytohormones, especially jasmonic acid (JA). Exogenous JA treatments mimicked the phenotypes of the oswrky28 mutants with inhibited root elongation and decreased arsenate/phosphate translocation. Our results suggested that OsWRKY28 affected arsenate/phosphate accumulation, root development at the seedling stage and fertility at the reproductive stage possibly by influencing homeostasis of JA or other phytohormones.